2015
DOI: 10.17986/blm.2015210947
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on Liver Injuries Caused by CPR Case Presentation

Abstract: Cardiac arrest is a life-threatening condition which requires fast maneuvers for saving the victim's life. Cardio-pulmonary resuscitation (CPR) is one of the easiest and handiest maneuver which proved many times to be savior even though sometimes it could worsen the victim's prognosis. In this paper the authors present the case of a 75-year old male, with a significant medical history and long term thrombolytic treatment who suffered a witnessed cardiac arrest. The emergency team who arrived at the victim's ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Liver lesions mostly occur in the form of a rupture and the reason for its more common occurrence on the left side is the fact that it corresponds to the area of focus in resuscitative chest compression and its relation to the liver anatomy [3,6,8]. Chest compression after rib and sternum fractures may affect the abdominal organs [9]. In our case the liver injury was observed on the left side closely neighbouring the rib fractures.…”
Section: Case Reportmentioning
confidence: 57%
“…Liver lesions mostly occur in the form of a rupture and the reason for its more common occurrence on the left side is the fact that it corresponds to the area of focus in resuscitative chest compression and its relation to the liver anatomy [3,6,8]. Chest compression after rib and sternum fractures may affect the abdominal organs [9]. In our case the liver injury was observed on the left side closely neighbouring the rib fractures.…”
Section: Case Reportmentioning
confidence: 57%
“…Similar assumptions are adopted by Martin et al 17 in a case study of patients with liver lacerations stemming from CPR. Contrary to this, Ioan et al 16 found that even when AHA guidelines were strictly followed in administering CPR, injuries and specifically liver lacerations were still found.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have indicated that internal organs may sustain injury during administration of CPR which comprise injuries of the thoracic wall, ribs, sternum, as well as organs located in chest area, e.g. pneumothorax, lung laceration [3][4][5][6][7][8][9][10][11][12][13][14][15] , abdominal organs especially the liver and spleen laceration [16][17][18][19] , and even the spinal cord have been reported. 20 In past autopsies conducted to determine a cause of death, it has been found that similarities exist between internal organ injuries sustained from CPR and those received from accidents or bodily abuse, which often complicates clear indication of cause and circumstance of death.…”
Section: Introductionmentioning
confidence: 99%